Interference with Murein Turnover Has No Effect on Growth but Reduces β-Lactamase Induction in Escherichia coli - Kraft, Angelika R. (American Society for Microbiology, 1999)
Physiological studies of a mutant of Escherichia coli lacking the three lytic transglycosylases Slt70, MltA, and MltB revealed that interference with murein turnover can prevent AmpC β-lactamase induction. The triple mutant, although growing normally, shows a dramatically reduced rate of murein turnover. Despite the reduction in the formation of low-molecular-weight murein turnover products, neither the rate of murein synthesis nor the amount of murein per cell was increased. This might be explained by assuming that during growth in the absence of the major lytic transglycosylases native murein strands are excised by the action of endopeptidases and directly reused without further breakdown to muropeptides. The reduced rate of murein turnover could be correlated with lowered cefoxitin-induced expression of β-lactamase, present on a plasmid carrying the ampC and ampR genes from Enterobacter cloacae. Overproduction of MltB stimulated β-lactamase induction, whereas specific inhibition of Slt70 by bulgecin repressed ampC expression. Thus, specific inhibitors of lytic transglycosylases can increase the potency of penicillins and cephalosporins against bacteria inducing AmpC-like β-lactamases.